Tinjauan Kekuatan Aksial dan Persyaratan Detailing Elemen Kolom Struktur Beton Bertulang Konvensional Berpengikat Sengkang Dengan Pembatasan Rasio Penulangan Berdasarkan SNI 2847:2019 Dengan Mempertimbangkan Aspek Kemudahan Praktik Di Lapangan dan Studio - Herry Prabowo; Mochammad Hilmy; Yudhiarma Yudhiarma (Politeknik Negeri Pontianak, 2021)
The The main parameters that determine the axial capacity of a reinforce concrete column include the dimensions of the column, the the quality of the concrete, the quality of steel reinforcement, the size of steel reinforcement, the amount of steel used. In practice, these parameters generally have a certain value so that for certain spans also the details of a reinforced concrete column can be estimated by taking parameters that exist in the field as constraints. The process of drawing and estimating detailed columns in a studio of architecture usually also refers to practical needs in the field. So by providing limits on span, concrete quality, and steel quality we can estimate the details of the column under review. The process of calculating beam dimensions is done by estimating the cross section height of the column (h) and the width of the column (b) according to the limitation of low-rise building. Calculation of dimensions of main tensile reinforcement is done by taking into account the distance of reinforcement in one line and the reinforcement ratio ductility.